Observational constraints on first-star nucleosynthesis: II. spectroscopy of an ultra metal-poor CEMP-no star - Placco, Vinicius M.; Christlieb, Norbert (Arxiv, 2016)
We report on the first high-resolution spectroscopic analysis of HE0020-1741, a bright (V=12.9), ultra metal-poor ([Fe/H] = -4.1), carbon-enhanced ([C/Fe] = +1.7) star selected from the Hamburg/ESO Survey. This star exhibits low abundances of neutron-capture elements ([Ba/Fe] = -1.1), and an absolute carbon abundance A(C) = 6.1; based on either criterion, HE0020-1741 is sub-classified as a CEMP-no star. We show that the light-element abundance pattern of HE0020-1741 is consistent with predicted yields from a massive (M = 21.5 Mo), primordial composition, supernova (SN) progenitor. We also compare the abundance patterns of other ultra metal-poor stars from the literature with available measures of C, N, Na, Mg, and Fe abundances with an extensive grid of SN models (covering the mass range 10 Mo - 100 Mo), in order to probe the nature of their likely stellar progenitors. Our results suggest that at least two classes of progenitors are required at [Fe/H] < -4.0, as the abundance patterns for more than half of the sample studied in this work (7 out of 12 stars) cannot be easily reproduced by the predicted yields.
Gesehen am 12.10.2017